Results of the Estimation of Biosimilarity of RinLiz® (LLC «GEROPHARM», Russia) and Humalog® (Lilly France, France) Using the Method of the Hyperinsulinemic Eulygemic Clamp on Healthy Voluntary - A. Yu. Mayorov; I. A. Fedotov; R. V. Drai; O. I. Avdeeva; I. E. Makarenko (Разработка и регистрация лекарственных средств)
Introduction. Insulin is the most effective hypoglycemic agent currently used in the clinical practice. Compared with recombinant human insulin, insulin lispro have a blood glucose profile that is much closer to physiological. The clinical trials program of insulin bioassays includes pharmacology studies: pharmacokinetics (PK), pharmacodynamics (PD), and a clinical safety study.Aim. To compare PK and PD of RinLiz® U100, solution for intravenous and subcutaneous administration (LLC «GEROFARM», Russia) and Humalog® U100, solution for intravenous and subcutaneous administration (Lilly France, France) in hyperinsulinemic euglycemic clamp.Materials and methods. This was randomized double-blind, two-arm crossover study in 28 healthy volunteers (NCT03604575). The studied preparations were injected before the clamp with a dose of 0.3 U/kg once subcutaneously in the area of subcutaneous fat in the anterior abdominal wall. During the study, regular blood sampling was performed; the amount of insulin lispro was determined by ELISA in the samples. The results of the determination were used to calculate the PK parameters and construct the curves «concentration – time». Based on the measurement of glycemia, the glucose infusion rate was adjusted. These data were used to calculate the PD parameters. The comparability of the studied drugs was considered proven if 90 % confidence intervals (CI) for the ratio of geometric mean PK parameters Cins. max and AUCins. 0-8 and 95 % CI for the ratio of geometric mean PD parameters GIRmax and AUCGIR0-8,5 were in the range of 80–125 %. Statistical data processing and presentation of the results was carried out using software packages R 3.4.2.Results and discussion. In the course of CI comparative PK and PD of RinLiz® and Humalog®, it was revealed that they have comparable PK and PD profiles. The CI for the logarithmically converted ratios of the values of the PK parameters was Cins. max 85.99–96.85 % and AUCins. 0-8 90.58–97.28 %, the PD of the parameters were 95.64–118.94 for GIRmax and 96.5–121.36 for AUCGIR0-8.5, all the CIs correspond to the set the boundaries of 80–125 % to establish comparability between RinLiz® and the original drug.Conclusion. The results demonstrated the high degree of similarity of RinLiz® U100 and Humalog® U100 in terms of PK, PD profiles and safety.